The bile acid chenodeoxycholic acid associates with reduced stroke in humans and mice - Vera F. Monteiro-Cardoso; Xin Yi Yeo; Han-Gyu Bae; David Castano Mayan; Mariam Wehbe; Sejin Lee; Kumar Krishna-K; Seung Hyun Baek; Leon F. Palomera; Lik Hang Wu; Leroy S. Pakkiri; Sangeetha Shanmugam; et al. (Journal of Lipid Research)
Bile acids are liver-derived signaling molecules that can be found in the brain, but their role there remains largely unknown. We found increased brain chenodeoxycholic acid (CDCA) in mice with absent 12α-hydroxylase (Cyp8b1), a bile acid synthesis enzyme. In these Cyp8b1−/−, and in Wt mice administered CDCA, stroke infarct area was reduced. Elevated glutamate-induced excitotoxicity mediated by aberrant N-methyl-D-aspartate receptor (NMDAR) overactivation contributes to neuronal death in ischemic stroke. We found reduced glutamate-induced excitotoxicity in neurons from Cyp8b1−/− and CDCA-treated Wt mice. CDCA decreased NMDAR-mediated excitatory post-synaptic currents by reducing over-activation of NMDAR subunit GluN2B in Wt brains. Synaptic NMDAR activity was also decreased in Cyp8b1−/− brains. Expression and synaptic distribution of GluN2B were unaltered in Cyp8b1−/− mice, suggesting CDCA may directly antagonize GluN2B-containing NMDARs. Supporting our findings, in a case-control cohort of acute ischemic stroke patients, we found lower circulatory CDCA. Together, our data suggest that CDCA, acting in the liver-brain axis, decreases GluN2B-containing NMDAR overactivation, contributing to neuroprotection in stroke.